Market value effects of acquisitions involving internet firms: a resource-based analysis - Uhlenbruck, Klaus; Hitt, Michael A.; Semadeni, Matthew (Strategic management journal, 2006)
While most prior research suggests that the average change in market value of acquiring firms varies closely around zero, recent research grounded in the resource-based view and organizational learning theory identify positive returns to acquirers. We contribute to this literature by focusing on acquisitions of Internet firms and the potential for the transfer of scarce resources. We hypothesize that acquisitions made by offline firms of Internet firms and by Internet firms of other Internet firms lead to positive market valuation for the acquirer. Results of an event study of 798 acquisitions of Internet firms provided support for these predictions. We also find that prior alliances with online firms do not reduce the gains from such acquisitions to offline firms.